PENGARUH POLA ASUH DAN MOTIVASI TERHADAP PRODUKTIVITAS KERJA GENERASI Z - Aulia, Pramitha; Moeliono, Nadya; Putri, Davina Azzaria Kusumo (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
Generation Z is the generation born after 1995 and grew up in an era of advanced technology. They have different characteristics from previous generations, such as being familiar with technology, enjoying working in teams, having a high sense of curiosity, and being hard workers. Therefore, work motivation and productivity are very important things to pay attention to in generation Z. One of the factors that influences work motivation and productivity in generation Z is the parenting style they have received since childhood. Parenting patterns can influence a person's personality development, values and attitudes towards the surrounding environment, including the work environment. The research method used was a survey with a questionnaire as a data collection instrument. Respondents in this study were generation Z employees in private companies and had worked for at least 1 year. Data analysis was carried out using simple linear regression techniques.